PENGELOLAAN PERPUSTAKAAN SEBAGAI PUSAT SUMBER BELAJAR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 012 SINGKEP BARAT - Fathullah; Siti Nursira Hidayani; Pauzi (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to determine library management as alearning resource center at SD Negeri 012 Singkep Barat and todetermine the factors that influence library management as alearning resource center at SD Negeri 012 Singkep Barat. Themethod used is a qualitative method with a phenomenologicalapproach. The research subjects were the principal and 2 teachersof SD Negeri 012 Singkep Barat. The object of research is librarymanagement as a learning resource center. Data collectiontechniques through interviews, observation, and documentation.The data analysis technique used is data reduction, datapresentation and conclusion. The results showed that librarymanagement at SD Negeri 012 Singkep Barat was not optimal. Oneof the inhibiting factors is the lack of budget and human resources(library staff) and the principle of library management as alearning resource center, of the 4 principles of PSB management,there are 3 principles that have been running well, namely theprinciples of information system management, productionmanagement, and management principles. While the principle ofservice management needs to be improved so that activities in thelibrary can run optimally. With good library management, theactivities in the library will run smoothly in accordance with themanagement functions and principles of library management as alearning resource center.